Purification and characterization of an extracellular beta-xylosidase from Pseudozyma hubeiensis NCIM 3574 (PhXyl), an unexplored yeast - Mhetras, Nutan; Liddell, Susan; Gokhale, Digambar (AMB Express, 2016)
This paper reports on the production of beta-xylosidase from an unexplored yeast, Pseudozyma hubeinsis. The expression of this enzyme could be induced by beech wood xylan when the yeast was grown at 27 degrees C. The enzyme was purified to homogeneity as a glycoprotein with 23 % glycosylation. The purification protocol involved ammonium sulphate precipitation, QAE-Sephadex A50 ion exchange chromatography and sephacryl-200 column chromatography which resulted in 8.3-fold purification with 53.12 % final recovery. The purified enzyme showed prominent single band on SDS-PAGE. It is a monomeric protein of 110 kDa molecular weight confirmed by SDS-PAGE followed by MALDI-TOF mass spectrometry (112.3 kDa). The enzyme was optimally active at 60 degrees C and pH 4.5 and stable at pH range (4-9) and at 50 degrees C for 4 h. Chemical modification studies revealed that active site of the purified enzyme comprised of carboxyl, tyrosine and tryptophan residues. The carboxyl residue is involved in catalysis and tryptophan residue is solely involved in substrate binding. The best match from the search of the NCBInr database was with gi vertical bar 808364558 glycoside hydrolase of Pseudozyma hubeiensis SY62 with 26 % sequence coverage confirming that it is a glycoside hydrolase/beta-glucosidase. From the search of customized SWISSPROT database, it was revealed that SWISSPROT does not contain any entries that are similar to the purified enzyme.

Greener L-lactic acid production through in situ extractive fermentation by an acid-tolerant Lactobacillus strain - Singhvi, Mamata S.; Zendo, Takeshi; Gokhale, Digambar; Sonomoto, Kenji (Applied Microbiology and Biotechnology, 2018)
Lactic acid (LA) fermentation requires a neutralizer for a physiologically acceptable range. However, a neutralizer generates a large amount of gypsum, an environmental pollutant. Furthermore, the downstream processing is complicated and expensive, comprising 50–70% of the total cost. We previously developed a Lactobacillus delbrueckii FM1, which can produce undissociated LA without neutralizer. Here, we improved FM1 by adaptive evolution at pH 4.5, which generated Adp FM1 showing an ~ 1.80-fold increase in LA production compared to FM1. The LA production via fed-batch fermentation yielded 36.2 g/L of LA, with a productivity of 0.500 g/L/h. However, cell viability was reduced due to the acidic pH and/or end-product inhibition. Therefore, an in situ LA recovery process using an extractive solvent was employed to maintain cell viability. Adp FM1 produced 49.2 g/L of LA via in situ LA-extractive fed-batch fermentation, which was ~ 1.4-fold higher than that without LA extraction. Adp FM1 provided a total LA productivity of 0.512 g/L/h in 96 h. Among the tested strains, Adp FM1 exhibited the highest H⁺-ATPase activity and a 415-fold increase in H⁺-ATPase gene expression compared to the parent strain. These results suggest that the in situ LA extractive fermentation process will ease downstream processing and prove to be a more economical and environmentally friendly option compared to the present fermentation. To our knowledge, this is the first report on the production of undissociated L-LA by Lactobacillus using an in situ recovery process, with high LA production levels and productivity.

Cold active lipases: biocatalytic tools for greener technology - Mhetras, Nutan; Mapare, Vidhyashri; Gokhale, Digambar (Applied Biochemistry and Biotechnology, 2021)
Lipases are enzymes that catalyze the ester bond hydrolysis in triglycerides with the release of fatty acids, mono- and diglycerides, and glycerol. The microbial lipases account for \$400 million market size in 2017 and it is expected to reach \$590 million by 2023. Many biotechnological processes are expedited at high temperatures and hence much research is dealt with thermostable enzymes. Cold active lipases are now gaining importance in the detergent, synthesis of chiral intermediates and frail/fragile compounds, and food and pharmaceutical industries. In addition, they consume less energy since they are active at low temperatures. These cold active lipases have not been commercially exploited so far compared to mesophilic and thermophilc lipases. Cold active lipases are distributed in microbes found at low temperatures. Only a few microbes were studied for the production of these enzymes. These cold-adapted enzymes show increased flexibility of their structures in response to freezing effect of the cold habitats. This review presents an update on cold-active lipases from microbial sources along with some structural features justifying high enzyme activity at low temperature. In addition, recent achievements on their use in various industries will also be discussed.
Keywords: Cold active lipases; Frail compounds; Psychrophilic microbes; Synthesis of chiral molecules

Sustainable biodiesel production: importance of feedstock resources and production methods - Mhetras, Nutan; Gokhale, Digambar (RSC Advances, 2025)
Biodiesel made from renewable feedstock can be considered as a renewable and sustainable alternative to fossil fuels. This review briefly covers the historical background on biodiesel and discusses the various renewable feedstock sources for biodiesel production. It also emphasizes the importance of not only the feedstock quality but also on biodiesel quality that satisfies the ASTM D6751 and EN 1421 standards. In addition, the review describes various methods for biodiesel production with major thrust on transesterification, which is the key process. It also highlights the use of different types of catalysts including acidic, basic, bi-functional, and enzymes in the transesterification reaction. The review concludes by emphasizing the importance of pursuing further research and development to address the challenges in developing low cost and eco-friendly processes for biodiesel production.